Imprenditore ed Università nello start-up di impresa: ruoli e relazioni critiche - Lorenzo Petretto (Premio Tesi di Dottorato, 2008)
For some years now the Universities have assumed a dynamic role in fostering the enhancement of enterprise, making a direct contribution to the strategic management of intellectual property and the transfer of research deliverables, as well as in the training of potential entrepreneurs and the creation of structures offering support to new enterprises. Through the elaboration of empirical evidence from two quite different and hardly comparable institutional contexts - the American Babson College and the Italian University of Florence - this study analyses the potential activities of entrepreneurial matrix, in terms of relations, resources and incentives, offered for the use of young businesses in the start-up phase.